2009
DOI: 10.1021/ic900498x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentadienyl/Alkoxo Ligand Exchange in Group 4 Metallocenes: A Convenient Route to Heterometallic Species

Abstract: A simple and efficient strategy for the synthesis of nonorganometallic heterometallic clusters from cheap organometallic precursors is reported. This unique synthetic method involves elimination of the cyclopentadienyl ring from Cp(2)MCl(2) (M = Ti, Zr, Hf) as CpH in the presence of M'L(2) or M'L'(2) (M' = Ca, Sr, Mn; CH(3)OCH(2)CH(2)OH = LH or (CH(3))(2)NCH(2)CH(2)OH = L'H) in an alcohol as a source of protons. In the reactions presented, a series of compounds, [Ca(4)Ti(2)(mu(6)-O)(mu(3),eta(2)-L)(8)(eta-L)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Please do not adjust margins Please do not adjust margins likewise organometallic reagents can react with pendant acidic OH groups on multidentate ligands. 13,14,19,[83][84][85][86] Bifunctional (ambidentante) linker ligands with differing coordination sites can allow for stepwise attachment of two different metals (one at either site 36 ) as shown in Zn-Ti SSP ({Zn(POBC)2Ti(O i Pr)3}2) (POBC-H = p-carboxybenzaldehyde oxime). 46,87 Similarly, utilising the affinity of benzene rings to coordinate to the Cr(CO)3 fragment allows the formation of Zn-Cr precursors [MeZnOCH2PhCr(CO)3]4 and [MeZnOCH(PhCr(CO)3)2]2, useful for ZnCr2O4 synthesis.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Please do not adjust margins Please do not adjust margins likewise organometallic reagents can react with pendant acidic OH groups on multidentate ligands. 13,14,19,[83][84][85][86] Bifunctional (ambidentante) linker ligands with differing coordination sites can allow for stepwise attachment of two different metals (one at either site 36 ) as shown in Zn-Ti SSP ({Zn(POBC)2Ti(O i Pr)3}2) (POBC-H = p-carboxybenzaldehyde oxime). 46,87 Similarly, utilising the affinity of benzene rings to coordinate to the Cr(CO)3 fragment allows the formation of Zn-Cr precursors [MeZnOCH2PhCr(CO)3]4 and [MeZnOCH(PhCr(CO)3)2]2, useful for ZnCr2O4 synthesis.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…We define this broad group of materials as complex metal oxides (CMOs) which include mixed-metal oxides (AxByOz), heterometal doped metal oxides (B:AxOy) or composite metal oxides with a mixture of oxide phases (AwOx/ByOz). Today, many types of mixed-metal oxides are accessible from SSPs including perovskites (ABO3), [10][11][12][13][14][15][16] pyrochlores (A2B2O7), 17 spinels (AB2O4), [18][19][20][21][22][23][24][25] metal vanadates [Mx(VO4)y], 26,27 feldspars (MAl2Si2O8) 28 and Aurivilius phases (Bi2O2)(An−1BnO3n+1). 29…”
Section: Introductionmentioning
confidence: 99%
“…The composition and structure of 3 were confirmed by physicochemical methodsi ncludinge lemental analysisa nd FTIR, 1 HNMR, and 13 CNMR spectroscopy.…”
Section: Syntheses and Structuresmentioning
confidence: 93%
“…[12] We recently showed that reactions of multimetal components and their transformation into ac omplex product by as ingle-step synthesis route are very attractive for preparing binary oxide nanomaterials. [13][14][15][16][17][18] Such heterometallic compounds with atypical combinations of elements have af ixed metal stoichiometry at the molecular level. [15] Thus, the composition of the oxide products after thermolysis can be easily predicted from the ratio of the metals.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last four decades, structurally authenticated group 4 heterometallic alkoxides have been intensively investigated because of their numerous practical applications in catalysis, as well as material and polymer chemistry. Various combinations of titanium group metals with alkali, alkaline earth, and transition metal elements have been reported. Most of these compounds involve alkaline earth derivatives.…”
Section: Introductionmentioning
confidence: 99%